Effect of electronic smoking (Vaping) on thyroid hormones level and lipid profile in men - N. Hasan; N. A. Nasser; A. D. Hussein; O. A. Mohsein (The Ukrainian Biochemical Journal)
In the last period, the market quickly became saturated with vaping devices available in many flavors and forms appealing to youth. Both traditional cigarette and e-cigarette smoking are known to potentially alter metabolic processes, including hormone production and to increase the risk of lung, heart and kidney diseases. The aim of the study was to estimate the level of thyroid hormones and lipids in the blood of young men who smoked traditional or e-cigarettes. A case-control study involved 200 men aged 24-25 years who smoked 5-7 h per day, divided into two groups (100 e-cigarette smokers and 100 cigarette smokers) and 50 healthy men who did not smoke. The levels of thyroid-stimulating hormone (TSH), free thyroxine (FT4), and free triiodothyronine (FT3) were measured using COBAS E411. The levels of total cholesterol, TG, LDL and HDL were estimated spectrophotometrically. No significant changes were found in thyroid hormone levels or lipid profiles, except for an increased TG content in the group of traditional cigarette smokers compared to the control group. Whereas in the blood of e-smokers, the increase in the level of FT3 and FT4 and a significant decrease in that of TSH, as well as the elevated content of total cholesterol, TG, and LDL, were detected compared to the control group. The results obtained indicate that e-smoking affects the function of the thyroid gland and lipid metabolism.